PEMANFAATAN SMART TV SEBAGAI MEDIA INTERAKTIF UNTUK MENGEMBANGKAN KETERAMPILAN KOMUNIKASI SISWA: kualitatif fenomenologis - Putri Januarti, Yunita; Ermiana, Ida; Darmiany (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the use of Smart TV as an interactive medium in developing communication skills of elementary school students and identify its supporting and inhibiting factors. The research uses a qualitative method with a phenomenological approach involving interviews, participatory observation, and documentation. The informants consist of students, teachers, and school principals who are directly involved in Smart TV-based learning. The results of the study show that Smart TV makes a positive contribution to increasing student motivation, focus, and communication stimulus through the presentation of multimodal materials such as educational videos, Wordwall applications, Liveworksheets, and internet browsers. This media helps students be more courageous in responding, acquiring new vocabulary, and engaging in classroom interactions. However, its effectiveness is still hampered by limited facilities (two units for the entire school), inconsistent frequency of use, affective barriers such as lack of confidence, and linguistic barriers due to the dominance of the use of the Sasak language in daily conversations. The practice of translanguaging carried out by teachers helps clarify the meaning of the material but needs to be directed to strengthen Indonesian-based academic communication skills. This study concludes that Smart TV has great potential to improve students' communication skills if managed systematically and supported by the right pedagogical strategy.